Wounds Care In Patients During The Covid 19 Pandemic Era - Zega, Petra Diansari; Bui, Thanh Loan; Manurung, Herna Rinayanti; Marliani, Marliani; Alfiani , Alfiani (Jurnal EduHealth, 2022)
Wound care is part of nursing management. During Covid-19, the practice of wound care decreased under normal conditions. Nursing management knowledge is needed on how to practice wound care during COVID-19 to provide a wound healing process. This systematic review aims to identify wound care nursing care management during COVID-19. Article searched from PubMed; ProQuest; and EBSCO; selected based on the following inclusion criteria: study focus on nurses practicing chronic wound care during Covid-19, focused nursing management, case studies, articles published in the 2019-2021 range, full text, articles in English. In the final stage, 5 articles were found. The results of the study show that nursing care management uses telehealth and telemedicine services for wound care patients. The findings of this systematic review indicate that telehealth and telemedicine services can provide opportunities to improve wound care to patients.